Development of the Russian socio-economic system: challenges and prospects - Alekseenko M. V., Golub I. I., Verenikina A. O., Terioshina V. V., Medvedeva N. V., Shpak A. S., Krutova O. V., Kashirin A. I., Poletaev I. V., Kruglov V. N., Tiutin D. V., Kruglov V. N., Petrov A. M. (Development of the Russian socio-economic system: challenges and prospects, 2024)
modern trends in the development of the world economy «force» the enterprises of the Russian Federation to look for new ways to activate their production capacities. The core of this revitalization is innovation activity. Innovations permeate all types of society's activities and are the main factor and incentive for the development and competitiveness of the country. The Russian economy has a high innovation potential, but the level of application of this potential and mastering of innovation processes is still not high enough. Innovation management is perceived by many specialists with distrust, which makes it difficult to choose a development path for the growth of innovation activity. In enterprises focused on the creation and implementation of innovations, this problem is very relevant. The study of the essence of innovative enterprises, the peculiarities of their functioning will improve the quality of their management, and, consequently, will increase the level of economic development.
Keywords: инновации; факторы развития; innovations; условия развития; функционирование; инновационные предприятия; innovative enterprises; development factors; functioning; development conditions